The Essential Ocean Variable Framework: GOOS authoritative guidance on observing system design - Palacz, Artur Piotr (Zenodo, 2022)
Presentation given on 31 March 2022 during the Arctic Observing Summit (AOS) 2022 meeting of Working Group 2: Regional to Global Observing. The talk introduced the Essential Ocean Variable (EOV) framework and how it is used by the Global Ocean Observing System (GOOS) to provide authoritative guidance on ocean observing system design, from requirement setting to coordination of observations and management of data and information products. Ongoing efforts to expand the framework (e.g. human impact on the ocean) and to better incorporate the needs of regional observations (e.g. deep ocean, Arctic) were highlighted, using examples of relevant developments as part of the H2020 ECOTIP and H2020 EuroSea projects.